Neuromuscular Manifestations of West Nile Virus Infection - Leis, A. Arturo; Stokic, Dobrivoje S. (Frontiers in Neurology, 2012)
The most common neuromuscular manifestation of West Nile virus (WNV) infection is a poliomyelitis syndrome with asymmetric paralysis variably involving one (monoparesis) to four limbs (quadriparesis), with or without brainstem involvement and respiratory failure. This syndrome of acute flaccid paralysis may occur without overt fever or meningoencephalitis. Although involvement of anterior horn cells in the spinal cord and motor neurons in the brainstem are the major sites of pathology responsible for neuromuscular signs, inflammation also may involve skeletal or cardiac muscle (myositis, myocarditis), motor axons (polyradiculitis), peripheral nerve (Guillain-Barré syndrome, brachial plexopathy). In addition, involvement of spinal sympathetic neurons and ganglia provides a plausible explanation for autonomic instability seen in some patients. Many patients also experience prolonged subjective generalized weakness and disabling fatigue. Despite recent evidence that WNV may persist long term in the central nervous system or periphery in animals, the evidence in humans is controversial. WNV persistence would be of great concern in immunosuppressed patients or in those with prolonged or recurrent symptoms. Support for the contention that WNV can lead to autoimmune disease arises from reports of patients presenting with various neuromuscular diseases that presumably involve autoimmune mechanisms (GBS, other demyelinating neu¬ropathies, myasthenia gravis, brachial plexopathies, stiff-person syndrome, and delayed or recurrent symptoms). Although there is no specific treatment or vaccine currently approved in humans, and the standard remains supportive care, drugs that can alter the cascade of immunobiochemical events leading to neuronal death may be potentially useful (high-dose corticosteroids, interferon preparations, and intravenous immune globulin containing WNV-specific antibodies). Human experience with these agents seems promising based on anecdotal reports.